2023
DOI: 10.1371/journal.pone.0280902
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of interventions in reducing belief in conspiracy theories: A systematic review

Abstract: Conspiracy beliefs have become a topic of increasing interest among behavioural researchers. While holding conspiracy beliefs has been associated with several detrimental social, personal, and health consequences, little research has been dedicated to systematically reviewing the methods that could reduce conspiracy beliefs. We conducted a systematic review to identify and assess interventions that have sought to counter conspiracy beliefs. Out of 25 studies (total N = 7179), we found that while the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Future studies would do well to assess a number of other participant variables like their endorsement of conspiracy theories, the participation in local and national politics as well as their personal behaviors associated with energy use and conservation. There has been a great deal of work on how to best address and combat conspiracy theories in general ( Lewandowsky et al, 2022 ; O’Mahony et al, 2023 ). By addressing these elements, the research community can play a pivotal role in aiding society’s transition toward a more informed and proactive stance on climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies would do well to assess a number of other participant variables like their endorsement of conspiracy theories, the participation in local and national politics as well as their personal behaviors associated with energy use and conservation. There has been a great deal of work on how to best address and combat conspiracy theories in general ( Lewandowsky et al, 2022 ; O’Mahony et al, 2023 ). By addressing these elements, the research community can play a pivotal role in aiding society’s transition toward a more informed and proactive stance on climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research has indicated that experimentally promoting analytical thinking and deliberation has been associated with fewer conspiracy beliefs (Bago et al, 2022;Swami et al, 2014) When we look at what works in terms of reducing belief in unviable conspiracy theories, it is also evident that critical thinking is an effective target for researchers. Indeed, in a recent systematic review, explicitly teaching critical thinking skills was found to be one of the most effective interventions (O'Mahony et al, 2023). Participants who enrolled in a pseudoscience class presented on a number of topics from UFOs, paranormal phenomena, and conspiracy theories and made arguments for and against their existence (Dyer & Hall, 2019).…”
Section: Proposing a New Approach To Measuring Conspiratorial Thinkingmentioning
confidence: 99%
“…Disinformation is a pervasive feature of the modern world 1 that is linked to negative social consequences that include public-health risks [2][3][4] , political radicalization 5,6 , violence [6][7][8] and adherence to conspiracy theories 8,9 . Consequently, there is a growing interest in comprehending how false information propagates across social networks [10][11][12] , including design of strategies to curb its impact [13][14][15][16] albeit with limited success 17 . However, there is also a lacuna in our knowledge regarding how individuals learn and update their beliefs based on exposure to potential disinformation.…”
Section: Introductionmentioning
confidence: 99%